Comparing total body lipid content of young‐of‐the‐year Steller sea lions among regions of contrasting population trends - Lorrie D. Rea; Brian S. Fadely; Sean D. Farley; Julie P. Avery; Wendy S. Dunlap‐Harding; Vicki K. Stegall; Carrie A. B. Eischens; Tom S. Gelatt; Kenneth W. Pitcher (Marine Mammal Science, 2016)
Steller sea lion ( Eumetopias jubatus ) young‐of‐the‐year ( YOY ) are nutritionally dependent upon their dam through the majority of their first year. Several indices of body condition were measured in YOY 1.5–9 mo of age captured in Southeast Alaska ( n = 122), the Gulf of Alaska ( n = 182), and the Aleutian Islands ( n = 38) to test the hypothesis that nutritional stress impacted the ability of adult female Steller sea lions to adequately nourish their late gestation YOY in the central Aleutian Islands in the early 2000s. Body mass (kg) and percent total body lipid content (% TBL ) increased with age in all three regions of Alaska that were sampled ( P P TBL measured by isotope dilution. The trend for Aleutian Island YOY to have larger body mass and larger body fat reserves are counter to what would be expected if dams were unable to adequately provision their late lactation YOY due to inadequate food availability in the central Aleutian Islands.

Age‐specific vibrissae growth rates: A tool for determining the timing of ecologically important events in Steller sea lions - Lorrie D. Rea; Aaron M. Christ; Alison B. Hayden; Vicki K. Stegall; Sean D. Farley; Craig A. Stricker; Jo‐Ann E. Mellish; John M. Maniscalco; Jason N. Waite; Vladimir N. Burkanov; Kenneth W. Pitcher (Marine Mammal Science, 2015)
Steller sea lions ( SSL ; Eumetopias jubatus ) grow their vibrissae continually, providing a multiyear record suitable for ecological and physiological studies based on stable isotopes. An accurate age‐specific vibrissae growth rate is essential for registering a chronology along the length of the record, and for interpreting the timing of ecologically important events. We utilized four methods to estimate the growth rate of vibrissae in fetal, rookery pup, young‐of‐the‐year ( YOY ), yearling, subadult, and adult SSL . The majority of vibrissae were collected from SSL live‐captured in Alaska and Russia between 2000 and 2013 ( n = 1,115), however, vibrissae were also collected from six adult SSL found dead on haul‐outs and rookeries during field excursions to increase the sample size of this underrepresented age group. Growth rates of vibrissae were generally slower in adult (0.44 ± 0.15 cm/mo) and subadult (0.61 ± 0.10 cm/mo) SSL than in YOY (0.87 ± 0.28 cm/mo) and fetal (0.73 ± 0.05 cm/mo) animals, but there was high individual variability in these growth rates within each age group. Some variability in vibrissae growth rates was attributed to the somatic growth rate of YOY sea lions between capture events ( P = 0.014, r 2 = 0.206, n = 29).

A FIELD‐BASED METHOD FOR ESTIMATING AGE IN FREE‐RANGING STELLER SEA LIONS ( EUMETOPIAS JUBATUS ) LESS THAN TWENTY‐FOUR MONTHS OF AGE - James C. King; Thomas S. Gelatt; Kenneth W. Pitcher; Grey W. Pendleton (Marine Mammal Science, 2007)
Studies of health, survival, and development of juvenile Alaskan Steller sea lions ( Eumetopias jubatus , SSL) require accurate estimates of age for wild‐captured animals. However, the value and accuracy of several potential predictors of age have not been assessed with data from known‐age free‐ranging animals. During 2001–2005, forty‐six individual SSL originally branded or tagged at ≤6 mo of age were recaptured by the Alaska Department of Fish and Game (ADF&G). Using a series of general linear models, we evaluated the ability of morphometrics measurements: permanent canine tooth length (CTL), diastema (DIAS), whisker length (WHIS), and dorsal standard length (DSL) to predict the age of forty‐six known‐age juveniles ( n = 46 ≤23 mo of age). Permanent CTL was the strongest individual predictor ( r 2 = 0.80); followed by DSL, DIAS, and WHIS ( r 2 = 0.70, 0.56, and 0.45, respectively). The inclusion of a single sample from a 44‐mo‐old sea lion suggested quadratic relationships between age and all predictors for older animals. Only models including CTL predicted age to within 6 mo of known age. The equation Age = (−3.0112 +[0.6726 * CTL]+[0.4965 * DIAS]) allows for accurate age estimates of SSL ≤23 mo for both sexes.

DEVELOPMENT OF DISPERSAL, MOVEMENT PATTERNS, AND HAUL‐OUT USE BY PUP AND JUVENILE STELLER SEA LIONS ( EUMETOPIAS JUBATUS ) IN ALASKA - Kimberly L. Raum‐Suryan; Michael J. Rehberg; Grey W. Pendleton; Kenneth W. Pitcher; Thomas S. Gelatt (Marine Mammal Science, 2004)
A bstract Population declines of Steller sea lions ( Eumetopias juhatus ) in western Alaska (west of 144°W) may be a result of reduced juvenile survival. We used satellite telemetry to study the at‐sea distribution and movement patterns of pup (1.6–11.9 mo) and juvenile (12.0–35.1 mo) Steller sea lions. We studied trip distance, duration, and interhaul‐out movements of sea lions in relation to age, sex, and month of year in the decreasing western population (WP; Prince William Sound, Kodiak, Aleutian Islands, Alaska) and the increasing eastern population (EP; Southeast Alaska). We deployed 103 satellite transmitters (29 WP; 74 EP) on sea lions between 1998 and 2001. Round trip distance and duration increased with age, trip distance was greater in the WP than the EP, trip duration was greater for females than males, and haul‐out use was clustered. Changes in round trip distance and duration occurred from April to June for all age classes studied indicating that the annual timing of weaning may be less variable than the age of weaning. Overall, 90% of round trips were ≤ 15 km from haul‐outs and 84% were

TRENDS IN ABUNDANCE OF ALASKA HARBOR SEALS, 1983–2001 - Robert J. Small; Grey W. Pendleton; Kenneth W. Pitcher (Marine Mammal Science, 2003)
A bstract We estimated trends in abundance of harbor seals ( Phoca vitulina richardsii ) using over dispersed, multinomial models and counts obtained during aerial surveys conducted during 1983–2001 in the Ketchikan, Sitka, Kodiak, and Bristol Bay areas of Alaska. Harbor seal numbers increased significantly at 7.4%/yr during 1983–1998 and 5.6%/yr during 1994–1998 in the Ketchikan area, and 6.6%/yr during 1993–2001 in the Kodiak area. Counts were stable (trends not significant) during 1984–2001 (0.7%/yr) and 1995–2001 (‐0.4%/yr) in Sitka, and during 1998–2001 (‐1.3%/yr) in Bristol Bay. The influence of covariates ( e.g. , survey date, tide height) on trend estimates was significant and varied among areas and across years, demonstrating the need to include covariates in statistical analyses to accurately estimate trend. Our increasing trend estimate for Kodiak represents the first documented increase in harbor seal numbers over a relatively expansive area in the Gulf of Alaska. However, the trend for the Gulf of Alaska stock is equivocal due to the continued decline in Prince William Sound. Similarly, the trend for the Southeast Alaska stock is equivocal based on our increasing (Ketchikan) and stable (Sitka) trend estimates, and a recent decline reported for Glacier Bay. The Bering Sea stock appears stable after a period of possible decline.

DISPERSAL, ROOKERY FIDELITY, AND METAPOPULATION STRUCTURE OF STELLER SEA LIONS ( EUMETOPIAS JUBATUS ) IN AN INCREASING AND A DECREASING POPULATION IN ALASKA - Kimberly L. Raum‐Suryan; Kenneth W. Pitcher; Donald G. Calkins; John L. Sease; Thomas R. Loughlin (Marine Mammal Science, 2002)
A bstract Over the past 24 yr, 8,596 Steller sea lion ( Eumetopias jubatus ) pups were branded on their natal rookeries throughout Alaska with the objectives of determining survival rates, recruitment, movements, and site fidelity. Our objectives here were to examine the extent of dispersal of Steller sea lions away from their natal rookeries, movements between stocks, and degree of natal rookery fidelity. Pups (

COUNTING STELLER SEA LION PUPS IN ALASKA: AN EVALUATION OF MEDIUMFORMAT, COLOR AERIAL PHOTOGRAPHY - Gary M. Snyder; Kenneth W. Pitcher; Wayne L. Perryman; Morgan S. Lynn (Marine Mammal Science, 2001)
A bstract Estimates of Steller sea lion ( Eumetopias jubatus ) pup production are valuable for estimating population trend and size. Currently in Alaska, pups are counted by visiting rookeries, driving older animals into the water, then walking through the rookeries and counting the pups, a highly disruptive procedure. At smaller rookeries, with good vantage points, pups are occasionally counted from the periphery of rookeries without disturbing the sea lions. We evaluated counts made from medium‐format, color, aerial photographs as an alternative to drive counts and peripheral counts. Neither the peripheral counts nor the aerial photographic counts disturbed animals on the rokeries. There were strong 1:1 linear relationships between photographic counts and drive counts ( r 2 = 0.966, P r 2 = 0.999, P

REDUCED BODY SIZE OF FEMALE STELLER SEA LIONS FROM A DECLINING POPULATION IN THE GULF OF ALASKA - Donald G. Calkins; Earl F. Becker; Kenneth W. Pitcher (Marine Mammal Science, 1998)
A bstract Nutritional stress is a leading hypothesis behind the decline in numbers of Steller sea lions in the Gulf of Alaska, the Aleutian Islands, and the Bering Sea. To evaluate this hypothesis we compared body growth of female Steller sea lions 1.0–13.9 yr of age collected in the Gulf of Alaska during two time periods, 1975–1978 just prior to or early in the decline and 1985–1986 when the decline was well established. We found that growth, as measured by standard length, axillary girth, and mass, was reduced during the 1980s, supporting the undernutrition hypothesis. We also found a suggestion of reduced growth in our 1970s and 1980s samples when compared to a collection of Steller sea lions obtained from the Gulf of Alaska in 1958. However, no direct link has been demonstrated between undernutrition and the actual decline in numbers.